STRIVING FOR INTEGRITY IN EDUCATIONAL POLICY-MAKING: AN ETHICAL METAPHOR - Walker, Keith (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1993)
This paper is about educational policy-making considerations that engage the emotional and intellectual energies of school administrators. Specifically, this article uses a swimming pool water purification metaphor to discuss how educational leaders may sustain the ethical integrity of their professional policy-making. The metaphor is designed to enhance the reader’s appreciation of the ethical considerations undertaken by school leaders as they seek to sharpen the policy justifications that accompany their policy decisions. This metaphor extends beyond the rational-technical limits of most filter metaphors to appreciate some of the more complex cultural variables inherent in school settings. Résumé Cet article porte sur les paramètres stratégiques de l’éducation qui engagent les énergies affectives et intellectuelles des administrateurs scolaires. En particulier, l’auteur utilise la métaphore de la purification de l’eau d’une piscine pour analyser la façon dont les dirigeants scolaires peuvent assurer l’intégrité morale de leurs stratégies professionnelles. Cette métaphore cherche à mieux faire comprendre au lecteur les paramètres éthiques dont doivent tenir compte les dirigeants scolaires lorsqu’ils cherchent à aiguiser les justifications stratégiques qui accompagnent leurs décisions. Cette métaphore dépasse les limites rationnelles-techniques de la plupart des métaphores "filtres" pour mieux faire comprendre ce naines des variables culturelles plus complexes inhérentes au milieu scolaire.